Remimazolam mitigates oxidative stress response in patients undergoing one-lung ventilation - Li, Shanshan; Sana, Siriguleng; Wang, Dan (Frontiers in Surgery, 2025)
IntroductionThe effectiveness of remimazolam in suppressing oxidative stress, inflammatory reactions, and its lung-protective effects in patients undergoing thoracic surgery with one-lung ventilation (OLV) remains unestablished. This study aimed to investigate the protective effects of remimazolam against oxidative stress and inflammatory damage in such patients.MethodsThis randomized controlled trial evaluated 88 patients with lung tumors who underwent single-lung ventilation for thoracoscopic lobectomy under general anesthesia. Patients were randomly divided into an experimental group (R group) and a control group (Con group), with 44 patients in each group. The R group received an intravenous injection of 0.2 mg/kg of remimazolam during anesthesia induction. During anesthesia maintenance, a continuous intravenous infusion of remimazolam at a rate of 0.2 mg/kg/h was administered. The Con group received routine anesthesia. Preoperative and postoperative levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), tumor necrosis factor alpha (TNF-α), and interleukin (IL)-6 were detected. Changes in blood pressure and heart rate were recorded at four time points: upon entering the operating room (T1), immediately after tracheal intubation (T2), immediately after incision (T3), and immediately after surgery completion (T4). The postoperative awakening time, post-anesthesia care unit (PACU) stay time, and frequency of adverse reactions were also recorded.ResultsPostoperatively, the R group exhibited significantly higher levels of SOD and GSH-Px, and significantly lower levels of TNF-α and IL-6 compared to the Con group (P < 0.01). At T2, the blood pressure and heart rate in R group were significantly higher than those in Con group (P < 0.01), whereas no differences were found between the two groups at other time points. There were no significant differences between the two groups in postoperative awakening time, PACU stay time, or incidence of adverse reactions.DiscussionLow-dose remimazolam (0.2 mg/kg) can provide protective effects against oxidative stress and inflammatory injuries in patients undergoing OLV, without affecting awakening time or PACU time.